2021
DOI: 10.1002/cyto.a.24506
|View full text |Cite
|
Sign up to set email alerts
|

Rac1/pSTAT3 expression: A pharmacodynamic marker panel as a first step toward optimization of thiopurine therapy in inflammatory bowel disease patients

Abstract: Thiopurine derivatives, such as azathioprine and mercaptopurine, are standard conventional treatment options in inflammatory bowel disease (IBD). Unfortunately, approximately half of patients discontinue thiopurine therapy within 2 years. To improve the prediction of clinical effectiveness, thiopurine therapy is currently optimized using therapeutic drug monitoring. Ras-related C3 botulinum toxin substrate 1 (Rac1) has been suggested as a potential pharmacodynamic marker of the thiopurine effect in lymphocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Data from healthy subjects were obtained from the previous laboratory validation study and were used as reference values 24 . Healthy subjects were defined by having no known history of auto-immune diseases, no fever or other clinical complaints of active disease, no use of immune suppressive medication and a C-Reactive Protein (CRP) concentration below 10 mg/L.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data from healthy subjects were obtained from the previous laboratory validation study and were used as reference values 24 . Healthy subjects were defined by having no known history of auto-immune diseases, no fever or other clinical complaints of active disease, no use of immune suppressive medication and a C-Reactive Protein (CRP) concentration below 10 mg/L.…”
Section: Methodsmentioning
confidence: 99%
“…Rac1/pSTAT3 measurement. Peripheral ethylenediamine tetraacetic acid (EDTA) blood samples were used for immunocytochemical labelling, as recently described 24 . In brief, after blood collection, blood cells were washed and prepared for analysis with flowcytometry.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The active thiopurine metabolite 6‐thioguanine triphosphate causes T cell apoptosis via Rac1 and the downstream transcription factor signal transducer and activator of transcription 3 (STAT3) (10). A recent study found a reduced pSTAT3 signaling in healthy participants and thiopurine‐treated IBD patients in remission compared to patients with active disease (11). More research is needed to establish the potential role of Rac1/STAT3 determination in thiopurine‐treated IBD patients.…”
Section: To the Editormentioning
confidence: 99%